Up in smoke - Abd Razak, Dzulkifli (2005)
IF only problems could be solved by the signing of international conventions and protocols, the future of the globe would be much assured to say the least. But unfortunately, this is not the case. The onus of translating the conventions and protocols into action and reality lies very much with the signatories. Such is the case when the former Health Minister signed the World Health Organisationsponsored Framework Convention on Tobacco Control (FCTC) in New York two years ago. It gave so much hope then that Malaysia had finally decided to wage a serious war against tobacco which has been killing its citizens by the tens of thousands annually. The Tak Nak campaign was launched in a grand way with an allocation of RM20 million per year for five years. There were a series of tough talks on how to curb smoking among youths in particular and a warning not to make Malaysia the hub of tobacco activities.